Good's buffers as novel phase-forming components of ionic-liquid-based aqueous biphasic systems - Luis, Andreia
Aiming at the development of self-buffering and benign extraction/separation processes, this work reports a novel class of aqueous biphasic systems (ABS) composed of ionic liquids (ILs) and organic biological buffers (Good's buffers, GBs). A large array of ILs and GBs was investigated, revealing than only the more hydrophobic and fluorinated ILs are able to form ABS. For these systems, the phase diagrams, tie-lines, tie-line lengths, and critical points were determined at 25 degrees C. The ABS were then evaluated as alternative liquid liquid extraction strategies for two amino acids (L-phenylalanine and L-tryptophan). The single-step extraction efficiencies for the GB-rich phase range between 22.4 and 100.0% (complete extraction). Contrarily to the most conventional IL-salt ABS, in most of the systems investigated, the amino acids preferentially migrate for the more biocompatible and hydrophilic GB-rich phase. Remarkably, in two of the studied ABS, L-phenylalanine completely partitions to the GB-rich phase while L-tryptophan shows a preferential affinity for the opposite phase. These results show that the extraction efficiencies of similar amino acids can be tailored by the design of the chemical structures of the phase-forming components, creating thus new possibilities for the use of IL-based ABS in biotechnological separations. (C) 2015 Elsevier B.V. All rights reserved.